Maximal aerobic and anaerobic power and time performance in 800 m double poling ergometer - Støren, Ø.; Sunde, A.; Helgerud, J.; Johansen, J.-M.; Gjerløw, L.-E.; Hjortland, H.; Støa, E. M. (European Journal of Applied Physiology, 2023)
The purpose of this study was to investigate to what extent aerobic power (MAP), maximal anaerobic power (MANP), anaerobic capacity measured as time to exhaustion at 130% MAP (TTE), and maximal accumulated oxygen deficit (MAOD) correlated with 800 m double poling time trial performance (800TT) in a ski ergometer. A second aim was to investigate the relationship between TTE and MAOD, and to what extent TTE and MAOD would relate to anaerobic power reserve (APR). Eighteen cross-country skiers were tested for peak oxygen uptake (VO2peak) and oxygen cost of double poling to assess MAP. Peak power measurements during a 100 m TT were performed to assess MANP. TTE and an 800TT with continuous VO2 measurements were performed to assess time performance and MAOD. All tests were performed on a ski ergometer. Both MAP and MANP correlated strongly (r = - 0.936 and - 0.922, respectively, p < 0.01) with 800TT. Neither TTE nor MAOD correlated with 800TT. TTE correlated moderately with MAOD, both in mL kg-1 and in %VO2peak (r = 0.559, p < 0.05 and 0.621, p < 0.01, respectively). Both TTE and MAOD seemed to be a product of APR. These results suggest focusing on MAP and MANP, but not anaerobic capacity to explain time performance in an event with approximately 3 min duration.